2016
DOI: 10.1080/14767058.2016.1199671
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of chemerin, leptin, and interleukin-18 in gestational diabetes mellitus

Abstract: High chemerin and leptin levels are seen in GDM which may be associated with subclinical inflammation suggesting a role in development of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
3
35
1
Order By: Relevance
“…Increased IL18 levels were detected in women with GDM and correlated with maternal obesity [25]. Fatima et al found that increased IL18 levels in women with GDM were correlated with low-grade inflammation and insulin resistance [26]. IL18 gene polymorphisms have been investigated among patients with type 1 and type 2 diabetes [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL18 levels were detected in women with GDM and correlated with maternal obesity [25]. Fatima et al found that increased IL18 levels in women with GDM were correlated with low-grade inflammation and insulin resistance [26]. IL18 gene polymorphisms have been investigated among patients with type 1 and type 2 diabetes [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 494 articles that were retrieved, 20 were included in the meta-analysis; four were apelin studies [4,6,7,11], nine were chemerin studies [5,8,15,16,[23][24][25][26][27], five were omentin studies [28][29][30][31][32], one study involved both apelin and omentin [12], and one study involved both chemerin and omentin [33]. The 20 studies enrolled 2981 participants, of which 1493 were GDM patients and 1488 were healthy pregnant women (controls) [4-8, 11, 12, 15, 16, 23-33] (Fig.…”
Section: Literature Research and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Leptin is increased in GDM 96,117,118 . Vaspin has also been documented to be increased in GDM by most authors who have studied this 119121 , though a report of no association also exists 122 .…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 94%
“…Vaspin has also been documented to be increased in GDM by most authors who have studied this 119121 , though a report of no association also exists 122 . Results of investigations into the association between serum chemerin and gestational diabetes have been mixed, with the majority of studies finding no effect 123126 , while two studies reported an elevation 118,127 , and at least one small study described a reduction in chemerin among women with GDM 128 . Many of the above authors reported that obesity was a stronger determinant than GDM of serum chemerin.…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 99%